Improving the performance of internal combustion engines through lubricant engineering - Taylor, O (2016)
Low friction lubricant development provides a worthwhile contribution to vehicle CO2 emission reduction. Conventional low friction lubricant development focuses on empirical processes using out dated engine technology and old test methods. This strategy is inefficient and restricts the lubricant's potential. A new method proposed in the present research combines tribological simulations with rig, engine and vehicle tests. This approach provides insights undocumented until now. The contribution to CO2 emission reduction from individual engine components on vehicle drive cycles that include warm-up is predicted using lubricants down to the new SAE 8 viscosity grade. A bearing model is used to design the lubricant's non Newtonian characteristics to achieve friction reduction. An isoviscous lubricant with a viscosity of 4.6 cSt is shown to achieve the minimum friction in the bearing. The research shows that by starting with lubricants having kinematic viscosities higher than this value, it is possible to improve lubricant performance by lowering viscosity index (VI), introducing shear thinning, or reducing the density and pressure viscosity coefficient. Conversely, for lubricants with lower starting viscosities it is shown that higher VI values, more shear-stable lubricants and higher densities and pressure viscosity coefficients are required. The model predicts that high oil film pressures occur in the bearing and cause significant local lubricant viscosity increase (300%), indicating that the lubricant's pressure viscosity behaviour is important here, despite the contact being conformal. Simulation and motored engine testing establishes lubricant behaviour in the piston-to-bore conjunction. This analysis identifies a poor correlation between measured and predicted values at low engine speeds. A rig-on-liner tribometer shows that this error is attributable to a deficiency in the simulation's characterisation of boundary regime friction. An oil pump test determines how a modern variable displacement oil pump (and its control system) responds to lowering viscosity. The hypothesis that low viscosity lubricants cause the parasitic load from this component to increase is disproven using this component-level rig test. Chassis dynamometer testing compares the CO2 reduction performance of lubricant thermal management systems to the values achieved by reducing the viscosity grade. CO2 reductions of between 0.4% and 1.0% are identified using a cold-start new European drive cycle (NEDC) with a 5W-30 preheated to 60°C and 90°C respectively. Reductions in CO2 emissions between 0.4% and 1.2% are found on the NEDC by lowering the oil fill volume from 5.1 L to 2.1 L. For the unmodified case, a 3.7% reduction in CO2 emissions is reported by reducing the viscosity grade from a 5W 30 to an SAE 8 in the NEDC. The performance of a novel external oil reservoir is simulated to understand its ability to retain oil temperature during the vehicle cool-down procedure. An oil temperature of 65°C at the end of the soak period (following a prior test where the oil was assumed to reach 90°C) is predicted by installing insulation to the reservoir and indicates that a viable method to achieve the CO2 benefits identified through lubricant preheating tests exists. A full vehicle model combines the outputs from each of these sub-models to predict lubricant performance on the NEDC the new World-wide harmonized light duty test cycle (WLTC). This new approach provides a tool that enables next generation low friction lubricants to be developed. The model predicts that an SAE 8 lubricant can reduce CO2 emissions by 2.8% on the NEDC and 1.9% on the WLTC compared to a 5W-30. A theoretical experiment, where all lubricant related friction was deleted from the simulation, predicts that lubricant-related CO2 emissions are 8.7% on the NEDC and reduce to 6.3% on the WLTC. These results indicate that the planned adoption of the WLTC in September 2017 reduces the potential contribution to CO2 emission reduction from lubricants by 28%.